CRIPT exonic deletion and a novel missense mutation in a female with short stature, dysmorphic features, microcephaly, and pigmentary abnormalities. Issue 8 (2nd June 2016) - Leduc, Magalie S.; Niu, Zhiyv; Bi, Weimin; Zhu, Wenmiao; Miloslavskaya, Irene; Chiang, Theodore; Streff, Haley; Seavitt, John R.; Murray, Stephen A.; Eng, Christine; Chan, Audrey; Yang, Yaping; et al.
Abstract : Mutations in CRIPT encoding cysteine‐rich PDZ domain‐binding protein are rare, and to date have been reported in only two patients with autosomal recessive primordial dwarfism and distinctive facies. Here, we describe a female with biallelic mutations in CRIPT presenting with postnatal growth retardation, global developmental delay, and dysmorphic features including frontal bossing, high forehead, and sparse hair and eyebrows. Additional clinical features included high myopia, admixed hyper‐ and hypopigmented macules primarily on the face, arms, and legs, and syndactyly of 4–5 toes bilaterally. Using whole exome sequencing (WES) and chromosomal microarray analysis (CMA), we detected a c.8G>A (p.C3Y) missense variant in exon 1 of the CRIPT gene inherited from the mother and a 1, 331 bp deletion encompassing exon 1, inherited from the father. The c.8G>A (p.C3Y) missense variant in CRIPT was apparently homozygous in the proband due to the exon 1 deletion. Our findings illustrate the clinical utility of combining WES with copy number variant (CNV) analysis to provide a molecular diagnosis to patients with rare Mendelian disorders. Our findings also illustrate the clinical spectrum of CRIPT related mutations. © 2016 Wiley Periodicals, Inc.